PENGARUH KOMPETENSI, LINGKUNGAN KERJA TERHADAP MOTIVASI DAN KINERJA KARYAWAN PADA PT. SUMATERA SYLVA LESTARI ESTATE PASIR PENGARAIAN - Fatma, Kurnia; Machasin, Machasin; Setiawan, Deny (Komunitas Manajemen Kompetitif, 2024)
This research was conducted at PT. Sumatra Sylva Lestari Estate Pasir Pengaraian, with research time in 2022. The aim of this research is to determine the influence of competency and work environment on employee motivation and performance at PT. Sumatra Sylva Lestari Estate Pasir Pengaraian. To achieve this goal, research was conducted using a sample of 99 respondents who were employees of PT. Sumatra Sylva Lestari Estate Pasir Pengaraian. The data collection technique in this research is through a questionnaire. The data analysis method uses multiple linear regression using a Likert scale and data testing is carried out using SPSS Version 22 software. The results of this research show that the Competency variable influences employee work motivation, the work environment variable influences work motivation, the Competency variable influences employee performance, The work environment variable influences employee performance, and the motivation variable influences employee performance. contribution of the influence of competence (X1) and work environment (X2) on work motivation (Y1) at PT. Sumatra Sylva Lestari Estate Pasir Pengaraian was 19.8% and contributed to the influence of competence (X1), work environment (X2) and work motivation (Y1) on employee performance (Y2) at PT. Sumatra Sylva Lestari Estate Pasir Pengaraian by 33%.